Mathematical Modeling Applications in Medical Cases: An Essential Tool for Discovery: A Review - Dunia Alawi Jarwan (Journal of Global Pharma Technology, 2016)
This paper discusses the important role that mathematics and mathematical models play in the current revolution of learning, together with the resource regarding science and computational power. The delivery note outlines the reasons in the back of thinking about the utility on mathematics after the field of Biology or Medicine namely an urgent need. The bill also highlights the ambitions or goals over its department over disciplines indicating that mathematics is a wealthy location regarding examination ranging out of coherent abstractions in imitation of concrete applications. The pointed out examples prove that: The sound over mathematics is remarkably powerful or flexible, then the modes of thinking discovered within mathematics perform spawn inconceivable insight within many phenomena as take up current life. In it review, we furnish quick records yet spotlight half concerning the necessary features regarding modeling between organic systems together with an emphasis over the lesson on excitable cells. We finish along with dialogue in relation to possibilities yet challenges because of mathematical modeling going forward. In a large sense, the comment is designed after help answer an easy however necessary query that theoreticians oft rear from interested however skeptical colleagues about the empirical side.Keywords: Mathematical modeling, Medical Cases, Biochemical signals